Perspectives on partnership: Highlights of a literature review - Horton, D.; Prain, Gordon; Thiele, Graham (2010)
Working in partnership has become central in efforts to address complex environmental, socio-economic, and technological problems. The terms partner or partnership appear more than 100 times in the Paris Declaration on Aid Effectiveness and more than 200 times in the version of the CGIAR's new Strategy and Results Framework presented at the recent Global Conference on Agricultural Research for Development. It is promoted as an effective means to mobilise the resources and capacities needed to generate knowledge, stimulate innovation and influence decision-making. Nevertheless, partnering is often experienced as timeconsuming and frustrating, and it has proved difficult to demonstrate its 'value added'. To improve partnering at the International Potato Center (CIP), we reviewed publications, evaluations and reports dealing with partnership. Rather than a single 'partnership literature' we found several different literatures that approach the subject from different perspectives. Several themes – relating to partnering processes vs. partnership structures, partnership dynamics, types of partnership, incentives for partnering, the key role of trust, power and equity issues, success factors and evaluation – cut across the distinct literatures. This ILAC Brief presents findings in each of these areas, notes some prominent knowledge gaps and identifies areas for future study.